Risk Assessment of a Hydrogen Refueling Station in an Urban Area - Kwak, Jongbeom; Lee, Haktae; Park, Somin; Park, Jaehyuk; Jung, Seungho (Energies, 2023)
After the Paris Agreement was signed in 2015, many countries worldwide focused on the hydrogen economy, aiming for eco-friendly and renewable energy by moving away from the existing carbon economy, which has been the primary source of global warming. Hydrogen is the most common element on Earth. As a light substance, hydrogen can diffuse quickly; however, it also has a small risk of explosion. Representative explosion accidents have included the Muskingum River Power Plant Vapor Cloud Explosion accident in 2007 and the Silver Eagle Refinery Vapor Cloud Explosion accident in 2009. In addition, there was an explosion in a hydrogen tank in Gangneung, Korea, in May 2019, and a hydrogen refueling station (HRS) in Norway exploded in 2018. Despite this risk, Korea is promoting the establishment of HRSs in major urban centers, including downtown areas and public buildings, by using the Regulatory Sandbox to install HRSs. This paper employed the Hydrogen Risk Assessment Model (HyRAM) of Sandia National Laboratories (SNL), a quantitative risk assessment (QRA) program specialized in hydrogen energy for HRSs installed in major urban hubs. A feasibility evaluation of the site conditions of an HRS was conducted using the French land use planning method based on the results obtained through evaluation using the HyRAM and the overpressure results of PHAST 8.0. After a risk assessment, we confirmed that an HRS would be considered safe, even if it was installed in the city center within a radius of influence of jet fires and overpressure.
Keywords: Explosion accidents; Hydrogen refueling stations; Hydrogen risk assessment model; Hydrogen risks; Quantitative risk assessment; Risk assessment - modelling; Risks assessments; hydrogen; hydrogen refueling station; hydrogen risk assessment model; HyRAM; quantitative risk assessment